2006
DOI: 10.1111/j.1471-6402.2006.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Female Sport Attrition in a Stereotypical Male Sport Within the Framework of Eccles's Expectancy–Value Model

Abstract: An empirical research study based upon the expectancy–value model of Eccles and colleagues (1983) investigated the effect of gender‐role orientations on psychological dimensions of female athletes' sport participation and the likelihood of their continued participation in a stereotypical masculine activity. The model (Eccles et al., 1983) posits that gender‐role orientation is linked to the intention to persist or discontinue sport participation, which is acted upon indirectly through mediation by two motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 49 publications
(103 reference statements)
2
49
0
5
Order By: Relevance
“…It was found operant among competitive females (Chalabaev et al 2008a), physical education teachers (Chalabaev et al 2009b), undergraduate students (Chalabaev et al 2008b), referees (Souchon et al 2004), and junior high school girls (Chalabaev et al 2009a). Finally, other studies indicated that adolescent girls practicing a competitive masculine gendered sport were more likely to be higher in masculinity orientation than were dropout athletes and that adolescent girls with a feminine gender orientation were more inclined to drop out their participation (Guillet et al 2000;Guillet et al 2006). Thus, the above introductory remarks concerning the United States seems also relevant for a country such as France.…”
Section: The Sport As a Masculine Gendered Social Context: A Glance Imentioning
confidence: 99%
“…It was found operant among competitive females (Chalabaev et al 2008a), physical education teachers (Chalabaev et al 2009b), undergraduate students (Chalabaev et al 2008b), referees (Souchon et al 2004), and junior high school girls (Chalabaev et al 2009a). Finally, other studies indicated that adolescent girls practicing a competitive masculine gendered sport were more likely to be higher in masculinity orientation than were dropout athletes and that adolescent girls with a feminine gender orientation were more inclined to drop out their participation (Guillet et al 2000;Guillet et al 2006). Thus, the above introductory remarks concerning the United States seems also relevant for a country such as France.…”
Section: The Sport As a Masculine Gendered Social Context: A Glance Imentioning
confidence: 99%
“…As far as the perceived competence and dispositional flow variables are concerned, their items were respectively parceled into three and four homogeneous groups to maintain some reasonable degrees of freedom. Moreover, following the example of previous studies that used structural equation models to study sport motivation (Guillet, Sarrazin, Fontayne, & Brustad, 2006;Ntoumanis, 2001), the ensuing arithmetic means were used as indicators. Hau and Marsh (2004) proposed the use of more than two parcels, if at all possible, to avoid problems in the model identification.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…Those tests and emphasis on "outcome performance" give an advantage to adolescents who mature earlier than their teammates, because they are likely to be larger, stronger and faster, due to being "relatively older and/or more mature" (Pearson, Naughton, & Torode, 2006;Reilly, Bangsbo, & Franks, 2000) or have had more opportunities for practice (Côté, Baker, & Abernethy, 2007;Wattie, Cobley, & Baker, 2008). Furthermore, the perception of competence and "potential" play a significant role in subsequent motivation (Guillet, Sarrazin, Fontayne, & Brustad, 2006;Harter, 1978). Children that are positively affected by a relative age advantage are likely to be perceived as the most talented in their age group.…”
Section: Introductionmentioning
confidence: 99%